The Meaning of Respect in Romantic Relationships Among Low-Income African American Adolescents. (September 2014) - Gowen, L. Kris; Catania, Joseph A.; Dolcini, M. Margaret; Harper, Gary W.
Although interpersonal respect is considered an important quality in successful romantic relationships, limited attention has been paid to this concept. We examined the meaning of respect in romantic relationships as conceptualized by low-income, sexually active, heterosexually identified, African American adolescents aged 15 to 17 ( N = 50). Qualitative analysis revealed meanings of respect within the romantic dyad that could be divided into three broad themes: (a) performance of pro-social behaviors within the dyad, (b) inhibition of antisocial behaviors (e.g., violence), and (c) showing respect in the community, either through avoidance of situations that might embarrass one's romantic partner or performance of pro-social acts in public contexts (e.g., with friends or family). Gender, social class, and cultural differences in displays of respect and their interpersonal functions are discussed. A conceptual model is proposed both to understand the potential role that respect plays in adolescents' lives and relationships and as a guide for future study.